2023
DOI: 10.7150/ijbs.77469
|View full text |Cite
|
Sign up to set email alerts
|

N-glycosylation-mediated CD147 accumulation induces cardiac fibrosis in the diabetic heart through ALK5 activation

Abstract: Emerging evidence has implicated the important role of fibrosis in diabetic cardiomyopathy (DCM), while the underlying mechanism remains unclear. Considering the distinct and overlapping roles of Cluster of Differentiation 147 (CD147) in the pathogenesis of fibrotic diseases, we aim to investigate the role of CD147 in the fibrosis of DCM and explore its underlying mechanism. AAV9-mediated cardiac-specific CD147 silencing attenuated cardiac fibrosis and cardiac function in diabetic mice. CD147 knockdown signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…As an extracellular matrix metalloproteinase inducer, CD147 has been reported to participate in tissue remodeling by regulating ECM deposition and degradation, cell adhesion, cell-cell interactions, and inducing myofibroblast differentiation [ 8 ]. Moreover, CD147 can modulate pulmonary fibrosis [ 22 ], liver fibrosis [ 23 ], cardiac fibrosis [ 24 ], along with regulation of MMPs, TGF-β1, α-SMA, or VEGF expression. Thus, whether and how anti-CD147 affect airway remodeling were investigated, and the result revealed that anti-CD147 treatment reduced airway goblet cell metaplasia, collagen deposition, and vascular remodeling in OVA-induced asthmatic mice, accompanied by inhibition of VEGF and α-SMA expression.…”
Section: Discussionmentioning
confidence: 99%
“…As an extracellular matrix metalloproteinase inducer, CD147 has been reported to participate in tissue remodeling by regulating ECM deposition and degradation, cell adhesion, cell-cell interactions, and inducing myofibroblast differentiation [ 8 ]. Moreover, CD147 can modulate pulmonary fibrosis [ 22 ], liver fibrosis [ 23 ], cardiac fibrosis [ 24 ], along with regulation of MMPs, TGF-β1, α-SMA, or VEGF expression. Thus, whether and how anti-CD147 affect airway remodeling were investigated, and the result revealed that anti-CD147 treatment reduced airway goblet cell metaplasia, collagen deposition, and vascular remodeling in OVA-induced asthmatic mice, accompanied by inhibition of VEGF and α-SMA expression.…”
Section: Discussionmentioning
confidence: 99%
“…And Li [ 21 ] observed by electron microscopy that THCQD could improve the ultrastructure of myogenic fibers and mitochondria in diabetic rat cardiac myocytes. Heart Injuries in DCM is associated with myocardial fibrosis, which is characterized by ventricular remodeling and interstitial fibrosis, ultimately leading to heart failure [ 37 ]. High blood glucose levels can alter cardiac metabolism and function, leading to cardiac stiffness, as well as systolic and relaxation dysfunction [ 38 ].…”
Section: Discussionmentioning
confidence: 99%